Changes of serum macro and trace element in hyperketonemic goats - C. Okulmus; D. Turan; O. Turkyılmaz; S. Kızıltepe (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT In this trial, changes in macro and trace element concentrations and the relationships between these changes and glucose (Glu), β-hydroxybutyrate (βHB) and non-esterified fatty acid (NEFA) parameters were evaluated in hyperketonemic goats. Goat blood serum submitted to the laboratory for routine metabolic profile test were used as the study material. Serum with βHB concentrations >0.8mmol/L constituted the hyperketonemia group and those with concentrations <0.8mmol/L constituted the control group. Trace element concentrations of serum samples were measured using inductively coupled plasma mass spectrometry (ICP-MS). Hyperketonemia group goats had significantly higher levels of βHB, NEFA and aspartate transaminase (AST) and lower levels of Glu, triglyceride (TG) and alkaline phosphatase (ALP) compared to control group goats (p range: 0.05-0.001). Serum calcium (Ca), magnesium (Mg), copper (Cu), zinc (Zn), nickel (Ni) and chromium (Cr) levels were lower, and cobalt (Co) levels were higher in the hyperketonemic group (p<0.05). In addition, some elements had significant correlations with βHB, NEFA and Glu, the main metabolic markers of ketosis (p<0.05). The results of this study showed that hyperketonemia induced significant changes in blood element hemostasis in goats and this process may be closely related to energy metabolism.